Nurturing positive mental health and wellbeing in educational settings – the PRICES model - Frazier, Tyralynn; Doyle Fosco, Sebrina L. (Frontiers in Public Health, 2024)
This article presents a comprehensive framework for the implementation of social and emotional learning (SEL) programs as a means of health promotion in educational settings, to positively impact student, school, and adult mental health and wellbeing across education. It emphasizes the profound impact of education on life trajectories and success definitions. Drawing inspiration from the Greek myth of Icarus and Maya Angelou’s poem “Still I Rise,” it explores contrasting notions of success and their consequences. Schools play a pivotal role in shaping students’ wellbeing across multiple dimensions and developmental stages. Because of this, holistic mental health and wellbeing promotion that takes a whole-school approach is critical. The paper introduces the PRICES framework (Preparation and Access, Restoration, Integration, Connection and Community, Educator Support, Strengths-Based Cultivation and Student Voice) as a comprehensive method for implementing SEL programs in educational systems. Each component of the PRICES framework is discussed in detail, emphasizing its role in fostering positive health promotion within schools. Examples of implementation plans that operationalize this model through a co-development process focusing on the Social, Emotional, and Ethical (SEE) Learning program are also presented. The PRICES model encourages a shift towards a more holistic approach to education, nurturing social and emotional development alongside academic achievement. By prioritizing wellbeing, fostering a sense of community, and integrating evidence based SEL interventions, schools can positively impact the mental health and overall flourishing of students and educators, contributing to thriving communities.